Pembuatan Bahan Bakar Padat Biomassa Dari Limbah Sampah Organik Dengan Teknologi Biodrying - Kautsar, Muhammad (Jurnal Riset, Inovasi, Teknologi & Terapan, 2025)
The increasing population causes the amount of waste and energy consumption to increase. A recovery concept is needed that can utilize the energy contained in waste into alternative energy, namely biodrying. Biodrying is a waste processing method that utilizes the activity of microorganisms in decomposing organic material. Densification and innovation were carried out to make storage and transportation easier by making solid biomass fuel pellets with an adhesive mixture. This research aims to determine the effect of biodrying residence time and arpus adhesive concentration on the quality of the solid biomass fuel produced, including several tests, namely ash content, water content, volatile content, and burning time based on SNI 8951-2020. The production of solid biomass fuel was carried out by varying the biodrying residence time of 7, 10, 14, 18, 21 days and the arpus adhesive concentration of 5, 10, 15, 20, 25%. The research results showed that the best and optimal product was obtained with a biodrying time of 18 days and an adhesive concentration of 10% with an ash content of 7.50%, a water content of 11.96%, a volatile content of 69.88% and a flash time of 25 minutes.